The impact of deracination on colonial zone: Nadine Gordimer’s July’s People - Khoshnood, Ali (Penerbit UKM, 2015)
One of Nadine Gordimer‟s major obsessions has been raising awareness about the unjust and discriminatory policy of apartheid law in South Africa. She has dramatised the history of her country in her fictions to expose more awareness and truth of the unfair political situation of her homeland to the world. This study explores Nadine Gordimer‟s July’s People to analyze the effects of an impromptu journey of the Smales, a white family, into their black servant‟s hinterland. Apartheid atrocities and racial segregations of the white government of South Africa caused an interregnum of white reign and consequently led to black insurgency, tumult, sudden abandonment of home and therefore displacement of the Smales family. This deracination into the primitive settlement of the black servant July renders the Smales family members to have a nostalgic feeling of returning to their metropolis home, which is a manifestation of their inability to assimilate with and adapt into black culture and standard of living. The aim of this study is to analyze the deep impact of unhomely sojourn on each member of the Smales family and on July, who feels a sense of in-betweenness after his regression from city life style to his village environment that is devoid of the city qualities and values. Even though the Smales family‟s authority, power and social prestige are diminished while they are in the black contact zone, they emerge to be the embodiment of the white civilization – modern, secure and hygienic, which are the modes of urban life standards.